2023
DOI: 10.1111/1365-2745.14077
|View full text |Cite
|
Sign up to set email alerts
|

Sandy seeds: Armour or invisibility cloak? Mucilage‐bound sand physically protects seeds from rodents and invertebrates

Abstract: 1. Seeds represent a stage of a plant's life cycle that is extremely vulnerable to predation, which unlike most vegetative herbivory, is fatal to the individual. As such, understanding the distribution and abundance of plants may rely on understanding seed defences: characteristics that make seeds more difficult for granivores to locate, less beneficial for granivores to consume or both.2. Seeds that produce mucilage are widespread, found across many families and species. Although short-term (single day) studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Seed mucilage is a common trait in angiosperms, and it appears to play roles in seed survival, dispersal, and germination (Fernandez‐Alonso et al., 2003 ; LoPresti et al., 2022 ; LoPresti et al., 2023 ; Tsai et al., 2021 , Western, 2012 ; Yang, Baskin, Baskin, & Huang, 2012 ). Seed mucilage has been associated with dry and semi‐arid environments (LoPresti et al., 2022 ; Yang, Baskin, Baskin, & Huang, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seed mucilage is a common trait in angiosperms, and it appears to play roles in seed survival, dispersal, and germination (Fernandez‐Alonso et al., 2003 ; LoPresti et al., 2022 ; LoPresti et al., 2023 ; Tsai et al., 2021 , Western, 2012 ; Yang, Baskin, Baskin, & Huang, 2012 ). Seed mucilage has been associated with dry and semi‐arid environments (LoPresti et al., 2022 ; Yang, Baskin, Baskin, & Huang, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys of plant communities in arid and semi‐environments indicate that 10%–32% of species produce seed mucilage (Table 1 and references therein). In dry, arid, and sandy environments, mucilage is proposed to adhere seeds to their surroundings and possibly retain water (Kreitschitz, 2009 ; LoPresti et al., 2023 ). Focused studies have shown species‐specific impacts of mucilage on seed ecology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations